DEVELOPMENT STRATEGIES FOR OPERATING LEASE IN THE DIGITAL ERA - Okprianti, Reny; Emilson, Nur Husni; Noviantri, Salsabila; Saputra, Dwi Angga; Pangestu, M. Agun; Putri, Elsa Apriliana; Anggara, Veri (JILPR Journal Indonesia Law and Policy Review, 2024)
Amidst the rapid development of the digital era, the strategy of developing a Lease (leasing) is key for companies to maintain competitiveness. Leases offer a solution to access assets without having to make direct purchases, reducing the financial burden that often hinders business growth. Technological changes, such as the use of artificial intelligence and the Internet of Things (IoT), have encouraged companies to shift from asset ownership to a service access model, which is more flexible and responsive to market needs. In addition, data security and compliance with tax and accounting regulations are very important in developing this strategy. Companies are required to integrate advanced technology and understand regulatory changes to protect sensitive information and meet fiscal obligations. By designing an adaptive and responsive strategy, companies can maximize the benefits of Leases, improve operational efficiency, and take advantage of opportunities in the digital era, so that they remain relevant in increasingly tight business competition.